DEVELOPMENT OF DIFFERENTIATED TEACHING MATERIALS BASED ON THE INDEPENDENT CURRICULUM TO ENHANCE STUDENTS’ KNOWLEDGE OF SUBSTANCE AND ITS CHANGES - Firda Rahmah; Syubhan Annur; Ellyna Hafizah (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2025)
It is widely acknowledged that it is imperative to accommodate the diverse characteristics of learners. However, empirical evidence suggests that the learning process has yet to fully consider the individual needs of students. This development research aims to determine the viability of differentiated teaching materials based on the independent curriculum to enhance students’ knowledge learning outcomes on substance and its changes in terms of validity, practicality, and effectiveness in an effort to accommodate the learning needs of diverse learners. The research method employed is Research and Development (R&D), utilizing the 4D development model (Define, Design, Development, & Disseminate). The data analysis techniques used include Aiken’s validity analysis, practicality analysis using percentages, and analysis of the effectiveness of knowledge learning outcomes using N-gain. The results showed that the developed teaching materials received a validity score of 0.83 (very valid), a practicality score of 90% (very practical), and an effectiveness score of 0.4 (medium/effective). It is evident, based on the analysis of these scores, that the teaching materials developed are of a high validity, practical nature and efficacy in facilitating the learning process of scientific concepts, substances and its changes.